Characterisation of anti-resonance in two-degree-of-freedom electromagnetic kinetic energy harvester, with modified electromagnetic model. (June 2018) - O'Riordan, Eoghan; Frizzell, Ronan; O'Connell, Diarmuid; Blokhina, Elena
This article presents a detailed approach to the analysis of a two-degree-of-freedom electromagnetic kinetic energy harvester. These systems use multiple disconnected masses that can impact each other and the harvester housing. This causes complex dynamics in the system as significant momentum is transferred between the masses and, ultimately, results in strongly nonlinear behaviour. One particular nonlinear phenomenon of interest, which has not been previously characterised, is anti-resonance. Observing this phenomenon is important as it highlights efficient energy transfer between the masses, and maximising its effect can be used to enhance the harvesters' overall performance. A range of mathematical techniques are used to better explain the concept of anti-resonance and how it can be used to improve the understanding of the system dynamics. In addition, the widely used model for electromagnetic transduction is amended to give a more precise representation of the transducer force for this embodiment of the kinetic energy harvester. This unique analysis yields a rich modelling approach that can be used to inform future kinetic energy harvester designs by identifying and optimising key design parameters. Comparisons are made with experimental measurements of a two-mass electromagnetic kinetic energy harvester, validating the modelling approach.